How glaucoma patient characteristics, self-efficacy and patient–provider communication are associated with eye drop technique. (25th August 2015) - Sayner, Robyn; Carpenter, Delesha M; Robin, Alan L; Blalock, Susan J; Muir, Kelly W; Vitko, Michelle; Hartnett, Mary Elizabeth; Lawrence, Scott D; Giangiacomo, Annette L; Tudor, Gail; Goldsmith, Jason A; Sleath, Betsy
Abstract: Objectives: The objective of this study was to examine the extent to which patient characteristics, eye drop technique self-efficacy, and ophthalmologist–patient communication about eye drop administration are associated with glaucoma patients' ability to instil a single drop, have the drop land in the eye, and avoid touching the applicator tip of the medication bottle to the eye or face while self-administering eye drops. Methods: Glaucoma patients ( n = 279) were recruited from six ophthalmology clinics. Medical visits were videotape-recorded. Afterwards, patients were interviewed and demonstrated administering an eye drop on a videotaped-recording. Generalized estimating equations were used to analyse the data. Key findings: Ophthalmologists provided eye drop administration instruction to 40 patients. Patients with more years of education were significantly more likely to both instil a single drop ( P = 0.017) and have the drop land in their eye ( P = 0.017). Women were significantly more likely to touch the applicator tip to their eyes or face ( P = 0.014). Patients with severe glaucoma ( P = 0.016), women ( P = 0.026), and patients who asked at least one eye drop administration question ( P = 0.001) were significantly less likely to instil a single drop. Patients with arthritis were significantly less likely to have the drop land in their eye ( P = 0.008). African American patients were significantly less likely to touch the applicator tip to their eyes or face ( P = 0.008). Conclusions: Some glaucoma patients have a difficult time self-administering eye drops. As so few patients received eye drop administration instruction from their providers, there is an opportunity for pharmacists to complement care.